PENERAPAN STRUKTUR TIGA BABAK DALAM PENULISAN NASKAH PADA PRODUKSI VIDEO FEATURE “PENJAGA NAPAS SENI WAYANG GOLEK” - Salsabila, Aisyah Cryshanty; Sugito, Toto; Mahameruaji, Jimi Narotama (AT-TAWASUL, 2025)
Scriptwriting plays a role in designing stories, scenarios, and narratives that form the basis for the production of various media, including video features. As the main guide for the production team, the script must be structured so that it can be easily understood. The purpose of this research is to analyze the three-act structure in writing the script of the video feature “Keeping the Breath of Wayang Golek Art” with the theme of Padepokan Giri Harja's efforts to maintain the existence of wayang golek in the midst of modernization. The method used is a three-act structure, which consists of Act I (Introduction) introducing the history of wayang golek and Padepokan Giri Harja, Act II (Conflict) describing the various challenges faced, and Act III (Resolution) showing solutions to maintain the sustainability of this art. The production process of this video feature goes through pre-production, production, and post-production stages. The application of this structure helps to build a systematic flow, maintain the continuity of the narrative, and strengthen the message to be conveyed. With a fact-based writing approach and effective storytelling strategies, it is hoped that this video feature can increase public awareness of the importance of preserving wayang golek as a cultural heritage that has historical and philosophical value for Indonesia